DNA Methylation and the Potential Role of Methyl-Containing Nutrients in Cardiovascular Diseases. (16th November 2017) - Liu, Gang; Bin, Peng; Wang, Tianwei; Ren, Wenkai; Zhong, Jin; Liang, Jun; Hu, Chien-An Andy; Zeng, Zhaoying; Yin, Yulong
Abstract : Patients suffering from cardiovascular diseases (CVDs) experience a low quality of life and increase pressure on healthcare systems both nationally and globally. DNA methylation, which refers to the pathway by which DNA methyltransferase facilitates the addition of a methyl group to DNA, is of critical importance in this respect primarily because the epigenetic modification is implicated in a range of serious conditions including atherosclerosis, CVDs, and cancer. Research findings indicate that the number of epigenetic alterations can be elicited (both in utero and in adults) through the administration of certain nutritional supplements, including folic acid and methionine; this is partly attributable to the effect employed by methyl-containing nutrients in DNA methylation. Thus, for the purpose of illuminating viable therapeutic measures and preventive strategies for CVDs, research should continue to explore the intricate associations that exist between epigenetic regulation and CVD pathogenesis. This review centers on an exposition of the mechanism by which DNA methylation takes place, the impact it has on a range of conditions, and the potential clinical value of nutrition, driven mainly by the observation that nutritional supplements such as folic acid can affect DNA methylation.